Analysis of Operational Delay and Additional Investment Costs, As An Investment Consideration - Dina Yunanda; Christiono Utomo; Maranatha Wijayaningtyas (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: This paper aims to Analysis of Operational Delay and Additional Investment Costs, As an Investment Consideration: Case in Malang Pandaan Toll Road. Design/methodology/approach: The method used is statistic-descriptive and the design used is cross sectional. Findings: 2 hypotheses are while the other is accepted. Research limitations/implications: Variables considered in this study are electronic word of mouth, brand image, brand trust, and interest in saving. The scope of work of the Pandaan Malang Toll Road project has a length of 38 + 488 km, passing through two regions in Figure 1. Practical implications: Results show that from the 2 hypotheses proposed. Originality/value: This paper is original. Paper type: This paper can be categorized as a case study.